2011
DOI: 10.1021/jp208119x
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Reactivity of CuNi Alloys toward H2O and CO Dissociation for an Efficient Water–Gas Shift: A DFT Study

Abstract: Density functional theory (DFT) calculations are employed to study H 2 O and CO dissociations on a set of CuNi bimetallic surfaces aiming at exploring the optimal Ni ensemble on Cu(111) for an efficient waterÀgas shift (WGS) process, i.e., splitting H 2 O with high reactivity and avoiding CO activation. We found that Ni additives in the Cu(111) surface layer including a Ni monomer can remarkably enhance water splitting. Meanwhile, H 2 O dissociation barriers (E act ) are strongly correlated with the H adsorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
62
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 54 publications
8
62
0
Order By: Relevance
“…The calculated barriers and reaction heats on pure metals are very close to recently reported values; Gan et al, [9] Phatak et al [21] , and Zhu et al [26] have reported a barrier of approximately 0.90 eV on Ni(111) for water dissociation. Our result on Cu is also consistent with earlier reports, that is, 1.28 eV by Wang and Nakamura, [22] 1.31 eV by Gan et al, [9] 1.40 eV by Wang et al [27] at the DFT-GGA and PW91 level, and 1.36 eV by Gokhale et al [7] at the DFT-GGA and PBE level.…”
Section: H 2 O Adsorption and Dissociation On Mono-and Bimetallic Sursupporting
confidence: 87%
See 4 more Smart Citations
“…The calculated barriers and reaction heats on pure metals are very close to recently reported values; Gan et al, [9] Phatak et al [21] , and Zhu et al [26] have reported a barrier of approximately 0.90 eV on Ni(111) for water dissociation. Our result on Cu is also consistent with earlier reports, that is, 1.28 eV by Wang and Nakamura, [22] 1.31 eV by Gan et al, [9] 1.40 eV by Wang et al [27] at the DFT-GGA and PW91 level, and 1.36 eV by Gokhale et al [7] at the DFT-GGA and PBE level.…”
Section: H 2 O Adsorption and Dissociation On Mono-and Bimetallic Sursupporting
confidence: 87%
“…Summarizing the previous endeavors on the WGS process catalyzed by Cu/Ni alloys, we found that some researchers [9,11] suggested adding Ni to Cu (denoted as Cu/Ni hereafter), whereas other researchers [19,20] believed that adding Cu to Ni (denoted as Ni/Cu hereafter) would enhance the catalytic performance. Thus, whether Cu/Ni or Ni/Cu is more efficient and suitable for catalyzing the WGS process can be confusing.…”
mentioning
confidence: 74%
See 3 more Smart Citations